PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA POP UP BOOK UNTUK MENINGKATKAN HASIL BELAJAR IPAS MATERI RANTAI MAKANAN PADA SISWA KELAS V SDN TAMANSARI 1 - Fatimatus Zahra; Didit Yulian Kadriyanto; Ribut Prastiwi Sriwijayanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Based on the preliminary analysis, low student learning outcomes on the food chain topic were caused by the use of less varied learning models and teacher-centered learning. This condition resulted in low student participation during the learning process, leading to unsatisfactory learning outcomes. Therefore, this study aimed to improve the learning outcomes of fifth-grade students on the food chain topic through the implementation of the Problem Based Learning (PBL) model assisted by Pop Up Book media. This study employed the Classroom Action Research (CAR) method, which was conducted in two cycles. Each cycle consisted of two meetings involving the stages of planning, action, observation, and reflection. The subjects of this study were 17 fifth-grade students of SDN Tamansari 1. Data were collected through learning outcome tests administered in each cycle to determine students’ improvement after the implementation of the action. The results showed a continuous improvement in students’ learning outcomes in each cycle. In the pre-test, only 3 students (17.65%) achieved mastery learning, while 14 students (82.35%) did not meet the minimum mastery criteria. In Cycle I, the number of students who achieved mastery increased to 8 students (47.06%), while 9 students (52.94%) had not yet achieved mastery. These results had not met the classical mastery criterion of 75% set by the school. In Cycle II, learning outcomes improved significantly, with 16 students (94.12%) achieving mastery and only 1 student (5.88%) not yet achieving mastery. Based on these findings, it can be concluded that the implementation of the Problem Based Learning (PBL) model assisted by Pop Up Book media effectively improved the learning outcomes of fifth-grade students on the food chain topic at SDN Tamansari 1.